PRAKTEK KEGIATAN PEDULI KEBERSIHANBERSAMA PARA KARYAWAN DI LINGKUNGAN VITKA HOLDING DIANTARANYA VITKA FITNESS CENTER, EXELCO, NASI KAPAU PAK NIN, RM. SEDERHANA DAN CAFÉ MOMO - Lubis, Arina Luthfini; Rais, Syafruddin; Supardi; Fatimah, Zahara (PUSLITABMAS-Politeknik Pariwisata Batamc, 2024)
Several lecturers are members of the community service team carrying out Hygiene Care Practice Activities with Employees in the Vitka Fitness Center, Excelso, Nasi Kapau Pak Nin, RM Simple, and Café Momo. This activity is very necessary and beneficial for a company, so all cleaning workers must take advantage of this training. This service is carried out by visiting the destination where the method is to analyze and solve the problem by providing theoretical and practical guidance which takes place in several Vitka Holding Housekeeping Departments. In this service, local supervisors act as companions for the workers who receive direction from the service team. The service members also provide direct direction to workers who are responsible for cleanliness in the Vitka Holding environment. This was done based on observations by management who assessed that the level of cleanliness in the work environment had decreased. Vitka Holding Housekeeping Department itself is one umbrella with the superior, leading, quality Batam Tourism Polytechnic which is a center for tourism education and development, especially in the hospitality sector which gave birth to housekeeping, no doubt located on Jalan Gajah Mada the Vitka City Complex, Tiban Batam, Riau Islands Province , which has 4 majors, namely Rooms Division Management, Cuisine Division Management, Culinary Division Management and Tourism Planning Management. The expected results of this training are that workers will be more skilled and competent in carrying out their work and provide comfort for all guests who visit the Vitka Holding environment.